FAKTOR-FAKTOR PEMBENTUK KEPUTUSAN PEMBELIAN KONSUMEN PADA PRODUK AMDK (Air Minum Dalam Kemasan) PELANGI DI SEMARANG - Febi Eninta Br Munthe; Djoko Setyabudi (Jurusan Ilmu Komunikasi, FISIP, Universitas Diponegoro, 2019)
Forming a good brand image on one‟s brand is very important for consumers to distinguish it from from other brands and to increase their interest in said brand. One of Indonesia‟s water bottle brand, Pelangi, promotes their products to be one that „share love through every bottle‟. Using Facebook and Instagram to launch their #letslivetolove campaign, the Pelangi brand aimed to increase youth‟s and netizens‟ interest in buying their products. However, a preliminary survey on 96 consumers who came from their target audience showed that the #letslivetolove campaign was not the reason why they bought Pelangi water bottle. Thus, this study aimed to find out what factors formed consumers‟ decision in purchasing Pelangi bottled water. This is an explorative study aimed to quantitatively analyse factors that might affect consumers‟ decision in purchasing a specific product. Review on past research studies revealed 32 factors that might affect consumer‟s purchasing decision. These factors were used to create a survey conducted on 96 participants who, either, previously purchased Pelangi bottled water. Participants were within the age range of 18-40 years and lived in Semarang and data analysis were done using SPSS-15. The initial 32 factors were then summarised into 8 grouping factors: tangibility, perception, lifestyle, identity, image, risk, competition, and awareness. The conclusion of this study is that from the eight new factors formed, it was found that the awareness factor (component 8) is the most appropriate factor to summarize 32 variables (factors).